The Effect of Demonstration Methods to Improve Science Thinking Skills In Children Aged 5-6 Years - Herlina Herlina; Syamsuardi Syamsuardi; Ahmad Syawaluddin; Sahade Sahade (Journal of Educational Science and Technology (EST), 2023)
The purpose of the study was to determine the effect of demonstration methods on improving the science process skills of children aged 5-6 years. Research method quasi-experimental quantitative method, with non-equivalent control group design by comparing pre-test and post-test scores of conventional learning classes with demonstration method learning classes. Number of samples: 18 students of group B, aged 5-6 TK Tunas Bangsa Makassar. Data was collected with an observation sheet in the form of a checklist. The collected data were analyzed with descriptive statistics and inferential statistics of the independent test of the t test sample. The results of statistical analysis descriptive the average score of classes taught by conventional methods is lower than classes taught using demonstration methods from the results of the study showed that the demonstration method was able to increase the average value of children's science thinking process skills. The results of the hypothesis test show that the value of P = sig 0.00 and the value of Tcalculate is greater than Ttabel, thus concluding that the demonstration method is able to improve the ability of science thinking process skills in TK Tunas Bangsa Makassar